Alteração da barreira morfofuncional intestinal pela hiperglicemia e modulação da alanil-glutamina na dinâmica hidroeletrolítica em modelo animal de diabetes com enteropatia e diarreia secretória - Siqueira, Francisco Júlio Werner dos Santos (2018)
Diabetes Mellitus type 1 (DM-1) is a chronic multifactorial syndrome that affects millions of patients worldwide. Its occurrence triggers innumerable functional and metabolic disorders, among them the intestinal epithelial barrier lesion, associated with the manifestation of diarrhea. The present study evaluated the pathobiology of the intestinal barrier injury triggered by DM-1 and investigated the efficacy of Alanil-glutamine-based solution (ALGLN) on the occurrence of acute secretory diarrhea in the animal model. Wistar rats (12 -16 weeks, weighing ± 300g), which were randomly divided into control (CTRL) and DM-1 groups. The DM-1 group was induced with intraperitoneal streptozotocin (70mg / kg). All animals were kept for 14 days in metabolic cages. At the end of the experimental protocol, bioimpedance, intestinal perfusion, amino acid and intestinal permeability tests (lactulose and mannitol test) were performed by high performance liquid chromatography (HPLC), as well as biochemical and histopathological investigations. In the intestinal tissue we evaluated the gene expression of Claudine-2, Claudine-15, Occludin and ZO-1 firm junction proteins; in addition to the SGLT-1, PEPT-1, NHE3, CFTR transporters. We also evaluated ALGLN solution in the hydroelectrolytic recovery of CTRL and DM1 animals and after induction of secretory diarrhea with 1μg / ml Cholera toxin through intestinal perfusion in the presence or absence of ringer, glucose (OMS) and ALGLN solutions. DM1 induced hyperglycemia (> 400mg / dL) associated with polydipsia, polyphagia, polyuria, loss of fat mass, lean mass and increase of villi and crypts of the small intestine; reduction of serum glutamine concentration, arginine, Ac. glutamic and alanine. Intestinal losses CTRL vs. DM1: Na + (-0.3564 ± 4.333 mEq vs. -14.42 ± 0.6168 mEq) K + (-0.4553 ± 0.1331 mEq vs. -1.052 ± 0.04292 mEq) 2,129 ± 3,264 mEq vs -12.73 ± 0.9536 mEq); Osm (-1.526 ± 8.454 mOsm / kg vs. -36.07 ± 2.138 mOsm / kg). There was reduction of losses after perfusion with ALGLN solution. DM-1 animals increased the intestinal permeability observed by increased Lactulose excretion (CTRL: 1.510 ± 0.2218 vs DM1: 8.502 ± 0.5271). The lac / man ratio confirmed this exacerbation of paracellular route transport (CTRL: 0.4183 ± 0.01474 vs DM1: 1.916 ± 0.2258). There was a reduction of the relative gene expression of Claudine-2 and -15 and increase of SGLT-1 mRNA. A secretory effect of cholera toxin on DM1 (Na + (-43.80 ± 4.809), K + (-2.508 ± 0.2069), Cl- (-35.97 ± 4.275), Osm: (-87, 82 ± 10.73)]. However, the ALGLN solution was able to reduce such hydroelectrolytic losses (Na + (-6.559 ± 1.127), K + (0.9492 ± 0.2036), Cl- (-3.013 ± 1.020), Osm: (-21.12 ± 5.630)]. From these results ALGLN proved to be efficient for hydroelectrolytic recovery during intestinal dysfunction in diabetes, thus showing reversion of the damage triggered by the cholera toxin. Thus, ALGLN is suggested as a future pharmacological tool for intervention of intestinal disorders triggered in DM-1 and cholera infections.